Amino Acid Residues in the GerAB Protein Important in the Function and Assembly of the Alanine Spore Germination Receptor of Bacillus subtilis 168 - Cooper, Gareth R. (American Society for Microbiology, 2011)
The paradigm gerA operon is required for endospore germination in response to l-alanine as the sole germinant, and the three protein products, GerAA, GerAB, and GerAC are predicted to form a receptor complex in the spore inner membrane. GerAB shows homology to the amino acid-polyamine-organocation (APC) family of single-component transporters and is predicted to be an integral membrane protein with 10 membrane-spanning helices. Site-directed mutations were introduced into the gerAB gene at its natural location on the chromosome. Alterations to some charged or potential helix-breaking residues within membrane spans affected receptor function dramatically. In some cases, this is likely to reflect the complete loss of the GerA receptor complex, as judged by the absence of the germinant receptor protein GerAC, which suggests that the altered GerAB protein itself may be unstable or that the altered structure destabilizes the complex. Mutants that have a null phenotype for l-alanine germination but retain GerAC protein at near-normal levels are more likely to define amino acid residues of functional, rather than structural, importance. Single-amino-acid substitutions in each of the GerAB and GerAA proteins can prevent incorporation of GerAC protein into the spore; this provides strong evidence that the proteins within a specific receptor interact and that these interactions are required for receptor assembly. The lipoprotein nature of the GerAC receptor subunit is also important; an amino acid change in the prelipoprotein signal sequence in the gerAC1 mutant results in the absence of GerAC protein from the spore.